Douleur Neuropathique 4 (DN4) stratifies possible and definite neuropathic pain after surgical peripheral nerve lesion - Aho, Tommi (My University, 2020)
Douleur Neuropathique 4 (DN4) is a screening questionnaire to help identify neuropathic pain (NP) in clinical practice and research. We tested the accuracy of the DN4 questionnaire in stratifying possible NP (pNP) and definite NP (dNP) in patients operated for breast cancer. We studied 163 patients from a longitudinal cohort of breast cancer operated patients 4-9 years after surgery. pNP or dNP were classified according to the NP grading system. Surgeon-verified intercostobrachial nerve resection was used as a confirmatory test for dNP. A receiver-operating characteristic (ROC) curve analysis was performed and the area under the curve (AUC) was calculated to test the diagnostic accuracy (sensitivity, specificity, positive and negative predictive values) of the DN4. Additionally, we studied clinical factors that associated with a positive screening outcome in the interview part of the DN4 (DN4i). DN4i and DN4 showed significant accuracy in stratifying patients with pNP or dNP with cut-off scores 3 and 4 resulting to sensitivity of 66.2% and 79.4% and specificity of 77.8% and 92.6%, respectively. pNP and dNP patients showed differences in sensory descriptors of pain according to DN4i items. Screening positive on DN4i associated with dNP and younger age. Full DN4 could stratify pNP and dNP patients in a chronic postsurgical NP patient group operated for breast cancer. Additionally, DN4i showed significant accuracy in stratifying pNP and dNP, but an examination is necessary to obtain proper accuracy. Demographic factors may have an impact on the screening outcome of DN4i.